AI and Mental Health: Navigating Ethical Challenges in Therapy and Diagnosis (Journal of responsible AI & ethics, 2026)
Artificial Intelligence (AI) has the potential to revolutionize the field of mental health care by improving both the diagnosis and treatment of mental health disorders. However, the integration of AI in therapy and mental health diagnosis presents several ethical challenges, such as ensuring privacy, addressing algorithmic biases, and maintaining the human element in care. This paper examines the ethical concerns associated with AI in mental health, particularly its impact on therapeutic practices and diagnostic accuracy. By analyzing current AI applications in mental health care, the paper explores how AI algorithms are used in both clinical settings and remote therapy, and the potential benefits and risks they pose. Through empirical research, case studies, and theoretical frameworks, the study investigates issues like data privacy, bias in AI models, and the ethical responsibilities of AI developers and health care professionals. The paper also discusses the potential for AI to enhance the effectiveness of therapy and early diagnosis while stressing the need for ethical frameworks to guide AI use in mental health.